Using Photovoice to Understand the Meaning of Social Participation as It Impacts Transitions for Student Veterans - (:unkn) unknown (My University, 2017)
Student veterans encounter a variety of social pressures that civilian students do not, making the transition from military life to student civilian challenging. The issue of military personnel transitioning to roles as student veterans is one that is relevant to occupational therapy, as the profession promotes social participation as a meaningful occupation. It has been found that veterans find social relationships to be a critical challenge in the process of transitioning to the university and the civilian world (Plach & Haertlein Sells, 2013). Additionally, this issue is important to occupational therapy as a factor in promoting mental health. Mental health disorders are common in the military, despite the stigma against them. Post-traumatic stress disorder, depression, traumatic brain injuries, substance use disorders, and suicide are all major causes of concern within the military population (Tanielian & Jaycox, 2008; Pickett et al., 2015; U.S. Department of Veterans Affairs Epidemiology Program, 2015). Social support has been shown to positively effect these disorders or their symptoms (Kalpakjian, Lam, Toussaint, Hansen Merbitz, 2004; Pietrzak et al., 2009; Southwick, Vythilingham, & Charney, 2005). This undertaking, the Student Veteran Social Participation Photovoice Project (SVSP3), aimed to provide participants with an opportunity to communicate their needs to the community through photovoice methodology. This methodology necessitates that participants take an active role in the research process, which facilitated self-expression, introspection, and exploration of the transition process. The project provides qualitative data that can be used to enhance the student veteran transition experience (from programs to support services and resources), to expand upon the literature on student veterans, and to promote occupational justice (defined as social change that better supports inclusion and the occupational needs of everyone in society) for the student veteran population (Braveman & Suarez-Balcazar, 2009).
Keywords: Military; Photovoice; Social Participation; Student; Transition; Veteran